Long-term benefit of immunotherapy in a patient with squamous lung cancer exhibiting mismatch repair deficient/high microsatellite instability/high tumor mutational burden: A case report and literature review - Li, Na; Wan, Zixuan; Lu, Dongyan; Chen, Ruilian; Ye, Xiaowei (Frontiers in Immunology, 2023)
Genetic mutations that cause the deficiency expression of mismatch repair, may result in microsatellite instability, which is common in colorectal carcinoma and gastric cancers as well as Lynch syndrome. Mismatch repair deficiency/high microsatellite instability (dMMR/MSI-H) predicts the tumor response to immune checkpoint inhibitors. However, few studies have evaluated the efficacy of immune checkpoint inhibitors in non-small cell lung cancer (NSCLC) patients with dMMR/MSI-H. In this work, we presented one advanced squamous lung cancer patient with dMMR/MSI-H and high tumor mutational burden (TMB-H) who obtained the long-term benefit from immunotherapy. We consider that NSCLC patient with dMMR/MSI-H can benefit from immune checkpoint inhibitors.